Impact of forced fatty acid synthesis on metabolism and physiology of Saccharomyces cerevisiae. Issue 8 (29th August 2018) - Gossing, Michael; Smialowska, Agata; Nielsen, Jens
Abstract: Nutrient sensing and signaling controls the cellular response to extracellular nutrients and intracellular metabolites. Nutrient-dependent regulation of metabolism ensures balanced energy production and expenditure. We show that disturbing energy balance by forcing fatty acid synthesis has profound impact on metabolism and physiology of the yeast cell. In addition to an expected increase in storage lipids, we observed increased β-oxidation and reduced amino acid biosynthesis, indicating increased activity of nutrient-sensitive kinase Snf1p. We also observed increased sensitivity to rapamycin as well as decreased ribosome biogenesis and translation, indicating reduced activity of nutrient-sensitive kinase target of rapamycin complex 1. Additionally, we detected increased levels of oxidative stress and lower levels of amino acids. This study provides detailed insight into cellular resource redistribution in response to forced fatty acid synthesis and enables optimized engineering of microbial lipid production. Abstract : Disturbing energy balance by forcing fatty acid synthesis alters activity of central nutrient signalling kinases, causes oxidative stress and activates the cell wall integrity signaling pathway.